Impact of oral health education by audio aids, braille and tactile models on the oral health status of visually impaired children of Bhopal City - Anjali Gautam; Ajay Bhambal; Swapnil Moghe (Wolters Kluwer Medknow Publications, 2018)
Context: Children with special needs face unique challenges in day-to-day practice. They are dependent on their close ones for everything. To improve oral hygiene in such visually impaired children, undue training and education are required. Braille is an important language for reading and writing for the visually impaired. It helps them understand and visualize the world via touch. Audio aids are being used to impart health education to the visually impaired. Tactile models help them perceive things which they cannot visualize and hence are an important learning tool. Aim: This study aimed to assess the improvement in oral hygiene by audio aids and Braille and tactile models in visually impaired children aged 6-16 years of Bhopal city. Settings and Design: This was a prospective study. Materials and Methods: Sixty visually impaired children aged 6-16 years were selected and randomly divided into three groups (20 children each). Group A: audio aids + Braille, Group B: audio aids + tactile models, and Group C: audio aids + Braille + tactile models. Instructions were given for maintaining good oral hygiene and brushing techniques were explained to all children. After 3 months' time, the oral hygiene status was recorded and compared using plaque and gingival index. Statistical Analysis Used: ANNOVA test was used. Results: The present study showed a decrease in the mean plaque and gingival scores at all time intervals in individual group as compared to that of the baseline that was statistically significant. Conclusions: The study depicts that the combination of audio aids, Braille and tactile models is an effective way to provide oral health education and improve oral health status of visually impaired children.